IEC 61850 and XMPP Communication Based Energy Management in Microgrids Considering Electric Vehicles - Mohd Asim Aftab (IEEE Access, 2018)
Electric vehicles (EVs) can act as flexible resources in grid due to their bidirectional power transfer capabilities. In microgrids, the bidirectional power transfer capability of EVs through proper scheduling can be utilized to improve reliability, security, and quality of supply. Optimal scheduling of EVs is generally managed and controlled through the energy management system of microgrid. Since microgrid energy management (EM)-based scheduling of EVs is data driven, an effective communication between different actors of EM is required. This paper presents a IEC 61850 communication-based EM in microgrids with integrated EVs. Furthermore, augmentation of existing IEC 61850-90-8 logical nodes of EV and its related equipment with new data objects to include information exchanges for discharging operation of EVs have been proposed. Finally, in this paper, XMPP-based communication approach and its mapping to the service models for EM problem has been demonstrated.